Drug Delivery from PCL/Chitosan Multilayer Coatings for Metallic Implants - Soares, I. (2022)
This work was partially funded by the FEDER funds through the COMPETE 2020 Program and National Funds through the FCT – Portuguese Foundation for Science and Technology under the projects UIDB/50025/2020-2023 (CENIMAT/I3N), and also partially supported by the project ERC-CoG-2014. The authors would like to thank the use of the traction machine at the Biomaterials Laboratory from the Soft and Bio-functional Materials Group (CENIMAT/I3N).